Three-dimensional structure of low density lipoproteins by electron cryomicroscopy - Orlova, Elena V. (The National Academy of Sciences, 1999)
Human low density lipoproteins (LDL) are the major cholesterol carriers in the blood. Elevated concentration of LDL is a major risk factor for atherosclerotic disease. Purified LDL particles appear heterogeneous in images obtained with a 400-kV electron cryomicroscope. Using multivariate statistical and cluster analyses, an ensemble of randomly oriented particle images has been subdivided into homogeneous subpopulations, and the largest subset was used for three-dimensional reconstruction. In contrast to the general belief that below the lipid phase-transition temperature (30°C) LDL are quasi-spherical microemulsion particles with a radially layered core-shell organization, our three-dimensional map shows that LDL have a well-defined and stable organization. Particles consist of a higher-density outer shell and lower-density inner lamellae-like layers that divide the core into compartments. The outer shell consists of apolipoprotein B-100, phospholipids, and some free cholesterol.